Impacto do Programa Bolsa-Família sobre o bem-estar das famílias beneficiadas no estado do Ceará - Rocha, Leonardo Andrade (2008)
The study assessed the impact of the Bolsa Família Program (PBF) on the welfare of families benefited in the state of Ceará in the year 2007. For this purpose, we used the lifting of primary data in the municipalities of Ocara, Quixadá, Itapipoca and Sobral. 80 questionnaires were used and 40 to benefit families and 40 families not to benefit ( potential beneficiaries) in each municipality selected. The secondary data collection was based on information from the Ministry of Development and Fight against Hunger (MDS), the Controller General Union (CGU), the Department of Basic Education of the State of Ceará (SEDUC) and the Office of Research and Strategy Economic do Ceará (IPECE). Based on a tabular analysis, testing and Student t-H, Kruskall-Wallis to compare the means and proportions respectively, and linear regression analysis, it was possible to measure the programme's impact on the beneficiary families in the state do Ceará. The results concerning the characteristics home confirmed the homogeneity of the groups selected family. The PBF has had positive impact on teh pillars of the local human capital, explained by the improving indicators of health, education and nutritional status of families benefited. Progress budget of households benefited through the transfer of resources has shown a particular attribute the condition of dependency of these families with the policy of social welfare of the state. This peculiar feature was assessed by the lower participation in activities of non-agricultural work and the average total income, compared to the other group receiving no family. The PBF also simulated an expansion in household wealth i9n the group receiving the benefits, revealing the significant impact of the programme on the pattern of behaviour of spent on purchase of durable goods. Thus, it can be conclued that the Family Scholarship Program has an important role on the welfare of families as a policy of short-term, however, there was no impact on the generation of employment and income to ensure that these families gradually desvinculam to the programme the long term.